2019
DOI: 10.1002/ijc.32353
|View full text |Cite
|
Sign up to set email alerts
|

Trends in frequency and outcome of high‐risk breast lesions at core needle biopsy in women recalled at biennial screening mammography, a multiinstitutional study

Abstract: Between January 1, 2011, and December 31, 2016, we studied the incidence, management and outcome of high‐risk breast lesions in a consecutive series of 376,519 screens of women who received biennial screening mammography. During the 6‐year period covered by the study, the proportion of women who underwent core needle biopsy (CNB) after recall remained fairly stable, ranging from 39.2% to 48.1% (mean: 44.2%, 5,212/11,783), whereas the proportion of high‐risk lesions at CNB (i.e., flat epithelial atypia, atypica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
2
12
2
Order By: Relevance
“…Even more females are diagnosed with benign breast lesions, [1][2][3][4] although exact prevalence data are lacking. Surgical excision of all highrisk lesions is performed in 2.5% of all recalled females after screening, 5 and over 70% of these excised lesions are benign lesions. 5 This does not even include females referred from the general physician with palpable lesions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more females are diagnosed with benign breast lesions, [1][2][3][4] although exact prevalence data are lacking. Surgical excision of all highrisk lesions is performed in 2.5% of all recalled females after screening, 5 and over 70% of these excised lesions are benign lesions. 5 This does not even include females referred from the general physician with palpable lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical excision of all highrisk lesions is performed in 2.5% of all recalled females after screening, 5 and over 70% of these excised lesions are benign lesions. 5 This does not even include females referred from the general physician with palpable lesions. Benign or high-risk lesion are excised if: (1) the lesion is symptomatic or (2) when there is the need for additional tissue for diagnostic purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In part due to the implementation of widespread screening mammography, CCLs have been increasingly recognized in stereotactic core needle biopsies (CNB) performed for the assessment of calcifications [ 2 , 3 , 4 , 5 ]. CCLs have been postulated to represent the earliest non-obligate precursor of low-grade invasive breast carcinomas as they share molecular alterations and often coexist with entities in the low-grade breast neoplasia pathway, including atypical ductal hyperplasia (ADH), lobular neoplasia (LN), low-grade ductal carcinoma in situ (DCIS) and tubular carcinoma [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Excision of these lesions is only indicated if it is symptomatic or for diagnostic purposes. [5][6][7][8] Surgical excision (SE) is still the most performed procedure for benign or high-risk breast lesions in the Netherlands. However, previous studies have shown that vacuum-assisted excision (VAE) is an alternative non-surgical treatment option for most of these lesions.…”
Section: Introductionmentioning
confidence: 99%